Microglia Polarization, Gene-Environment Interactions and Wnt/β-Catenin Signaling: Emerging Roles of Glia-Neuron and Glia-Stem/Neuroprogenitor Crosstalk for Dopaminergic Neurorestoration in Aged Parkinsonian Brain - L'Episcopo, Francesca; Tirolo, Cataldo; Serapide, Maria F.; Caniglia, Salvatore; Testa, Nunzio; Leggio, Loredana; Vivarelli, Silvia; Iraci, Nunzio; Pluchino, Stefano; Marchetti, Bianca (Frontiers in Aging Neuroscience, 2018)
Neuroinflammatory processes are recognized key contributory factors in Parkinson’s disease (PD) physiopathology. While the causes responsible for the progressive loss of midbrain dopaminergic (mDA) neuronal cell bodies in the subtantia nigra pars compacta are poorly understood, aging, genetics, environmental toxicity, and particularly inflammation, represent prominent etiological factors in PD development. Especially, reactive astrocytes, microglial cells, and infiltrating monocyte-derived macrophages play dual beneficial/harmful effects, via a panel of pro- or anti-inflammatory cytokines, chemokines, neurotrophic and neurogenic transcription factors. Notably, with age, microglia may adopt a potent neurotoxic, pro-inflammatory “primed” (M1) phenotype when challenged with inflammatory or neurotoxic stimuli that hamper brain’s own restorative potential and inhibit endogenous neurorepair mechanisms. In the last decade we have provided evidence for a major role of microglial crosstalk with astrocytes, mDA neurons and neural stem progenitor cells (NSCs) in the MPTP- (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine-) mouse model of PD, and identified Wnt/β-catenin signalling, a pivotal morphogen for mDA neurodevelopment, neuroprotection, and neuroinflammatory modulation, as a critical actor in glia-neuron and glia-NSCs crosstalk. With age however, Wnt signalling and glia-NSC-neuron crosstalk become dysfunctional with harmful consequences for mDA neuron plasticity and repair. These findings are of importance given the deregulation of Wnt signalling in PD and the emerging link between most PD related genes, Wnt signalling and inflammation. Especially, in light of the expanding field of microRNAs and inflammatory PD-related genes as modulators of microglial-proinflammatory status, uncovering the complex molecular circuitry linking PD and neuroinflammation will permit the identification of new druggable targets for the cure of the disease. Here we summarize recent findings unveiling major microglial inflammatory and oxidative stress pathways converging in the regulation of Wnt/β-catenin signalling, and reciprocally, the ability of Wnt signalling pathways to modulate microglial activation in PD. Unravelling the key factors and conditons promoting the switch of the proinflammatory M1 microglia status into a neuroprotective and regenerative M2 phenotype will have important consequences for neuroimmune interactions and neuronal outcome under inflammatory and/or neurodegenerative conditions.